Adjuvant alternative cytokine-induced killer cell combined with natural killer cell immunotherapy improves the prognosis of post-mastectomy breast cancer - Yang, Xinyi; Weng, Desheng; Pan, Qiuzhong; Xiang, Tong; Yang, Chaopin; Wu, Zhengrong; Li, Minxing; Xie, Songzuo; Tang, Yan; Xia, Jianchuan; Zhao, Jingjing (Frontiers in Immunology, 2022)
Breast cancer is one of the most common cancers in women. Triple-negative breast cancer (TNBC) has a significantly worse prognosis due to the lack of endocrine receptors including estrogen receptor (ER) and progesterone receptor (PR) and human epidermal growth factor receptor 2 (HER2). In this study, we investigated adjuvant cellular immunotherapy (CIT) in patients with post-mastectomy breast cancer. We enrolled 214 post-mastectomy breast cancer patients, including 107 patients in the control group (who received chemotherapy/radiotherapy/endocrine therapy) and the other 107 patients in the CIT group (who received chemotherapy/radiotherapy/endocrine therapy and subsequent immune cell infusion). Of these 214 patients, 54 had TNBC, including 26 patients in the control group and 28 patients in the CIT group. Survival analysis showed that the overall survival rate of patients treated with cellular immunotherapy was higher than that of patients who were not treated with CIT. Compared to those who received cytokine-induced killer (CIK) cells alone, the patients who received CIK combined with natural killer (NK) cell immunotherapy showed the best overall survival rate. In subgroup analyses, adjuvant CIT significantly improved the overall survival of patients in the TNBC subgroup and the patients who were aged over 50 years. Our study indicates that adjuvant CIK cell combined with NK cell treatment is an effective therapeutic strategy to prolong the survival of post-mastectomy patients, particularly for TNBC patients and those who are aged over 50 years.